(untitled) (Philological Studies, 2019)
The paper is dedicated to the discussion of classification and cluster analysis as methods of text perception studies in linguistics and psycholinguistics. It emphasizes in particular that naïve classifications of speech material make clear the criteria for class formation. In cognitive psychology two types of classifications were determined: hierarchical and situational. The last one is preferred by subjects in the experiment of free classification of texts and slogans. Thanks to our experiment we found out that the main criteria for class formation is the topic of a text. The errors and mistakes do not play significant role in text perception in mass media discourse.